Risk assessment and early prediction of intraventricular hemorrhage in extremely preterm infants - Yueju Cai; Xiaolan Li; Xiaopeng Zhao; Yanyan Song; Wei Zhou (Scientific Reports)
Abstract This study aimed to identify the risk factors associated with intraventricular hemorrhage (IVH) in extremely preterm infants (EPIs), focusing on early-stage prediction to improve clinical outcomes. A retrospective cohort study was conducted at Guangzhou Women and Children’s Medical Center, including 189 EPIs born between January 2019 and December 2023. Infants were categorized into IVH and non-IVH groups based on head ultrasound findings. Risk factors were assessed using univariate and multivariate analyses, and a predictive model for IVH was developed. Of the 189 EPIs, 80 (42.3%) developed IVH, with 26 (13.8%) experiencing severe IVH. Gestational age was identified as a significant protective factor (OR = 0.565, p = 0.023), while invasive mechanical ventilation (IMV) was a key risk factor (OR = 2.718, p = 0.012). The predictive model demonstrated good performance, with an AUC of 0.753 (95% CI: 0.681–0.825). Gestational age and IMV are critical factors in the development of IVH in EPIs. Early identification of high-risk infants based on these factors can aid in timely interventions to reduce IVH incidence and improve outcomes.